Improving the detection of Helicobacter pylori in biopsies of chronic gastritis: a comparative analysis of H&E, methylene blue, Warthin-Starry, immunohistochemistry, and quantum dots immunohistochemistry - Wan, Weisong; Wang, Le; Liu, Yufei; Hu, Yuchang (Frontiers in Oncology, 2023)
The objective of the study was to compare the consistencyreliability of various staining methods, including H&E, Methylene Blue, Warthin-Starry (W-S), Immunohistochemistry (IHC) and Quantum dots immunohistochemistry (QDs-IHC), in detecting Helicobacter pylori (HP) in cases of mild, moderate and severe chronic gastritis.Methods: Biopsy samples were obtained from 225 patients with chronic gastritis at the Department of Pathology, Yichang Central People's Hospital between January 2019 and October 2019. The presence of HP was detected using H&E, Methylene Blue, W-S, IHC, and QDs-IHC.The positive rates for HP detection using H&E, Methylene Blue, W-S, IHC, and QDs-IHC were 42.22%, 51.11%, 53.78%, 59.11%, and 58.67%, respectively. In cases of mild chronic gastritis, the consistency of test results between H&E, Methylene Blue, W-S, and QDs-IHC with IHC were Kappa=0.196, P=0.033, Kappa=0.706, P<0.001, Kappa=0.717, P<0.001, and Kappa=0.968, P<0.001, respectively. Similarly, in cases of moderate chronic gastritis, Kappa values between H&E, Methylene Blue, W-S, and QDs-IHC with IHC were 0.356, P<0.001, 0.655, P<0.001, 0.741, P<0.001, and 0.946, P<0.001, respectively. For cases of severe chronic gastritis, the Kappa values between the staining methods and IHC were 0.271, P=0.037, 0.421, P=0.002, 0.621, P<0.001, and 1, P< 0.001, respectively.The study showed that the positivity rate of IHC was significantly higher than that of H&E, Methylene Blue, and W-S in detecting HP infection in chronic gastritis cases. In terms of consistency with IHC, QDs-IHC was the most reliable staining method across all severity grades, while the agreement between H&E and IHC was poor, and that between Methylene Blue and W-S with IHC was average. Pathology departments may choose the most appropriate staining method based on their specific needs, considering the staining time, contrast, and cost of each method.